Preparation method of novel loose composite nanofiltration membrane and application of novel loose composite nanofiltration membrane in dye wastewater treatment

By introducing Cu-HHTP into the nanofiltration membrane and adjusting the polymerization conditions, a new loose composite nanofiltration membrane was prepared, which solved the problems of low permeability and high divalent salt repulsion in the existing nanofiltration membrane, and achieved efficient dye and salt separation effect.

CN119680409APending Publication Date: 2025-03-25JIANGSU LONGMEM ENVIRONMENTAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311238894.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

When treating textile wastewater, the existing nanofiltration membrane has a low permeability and high repulsion to divalent salts, making it impossible to effectively separate dyes and salts.

Method used

Using the preparation method of a new loose composite nanofiltration membrane, a loose TFN nanofiltration membrane was prepared on the PES base membrane through monomer synthesis, aqueous and organic phase solution configuration and interface polymerization technology, and a loose TFN nanofiltration membrane was prepared on the PES base membrane to adjust the Cu-HHTP content and polymerization time to adjust the porous structure of the membrane.

Benefits of technology

The water permeability and dye removal rate of the membrane are improved, while the repulsion to divalent salts is reduced, effective fractionation of dyes and salts is achieved, and the treatment effect of dye wastewater is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119680409A_ABST
    Figure CN119680409A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of membrane separation, and relates to a preparation method of a novel loose composite nanofiltration membrane, which is used for treating dye wastewater, and specifically comprises the following steps: firstly preparing an aqueous phase solution, dissolving MOF (CU-HHPT) with different contents in a PIP aqueous solution, then depositing the aqueous phase solution on the surface of a PES support layer for a certain time, and drying at normal temperature. Then carrying out crosslinking for a certain time by using an organic phase (n-hexane) solution containing trimesoyl chloride (TMC), pouring out the organic solution, washing the surface of the membrane by using the n-hexane solution, and then carrying out curing treatment; and finally, soaking in deionized water (DI) for subsequent use. According to the invention, the composite nanofiltration membrane with high performance is prepared on the PES supporting layer through synthesis of CU-HHPT, co-deposition of a water-phase solution and interfacial polymerization. According to the membrane prepared by the method, the pure water permeability is obviously improved, the high retention rate of dye is kept, and salt is allowed to permeate; the composite nanofiltration membrane has very important practical significance in the field of dye wastewater treatment or sewage treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of membrane separation and relates to a preparation method of a novel loose composite nanofiltration membrane for efficiently purifying dye wastewater. Background Art

[0002] As one of the world's important manufacturing industries, the textile industry provides people with a rich variety of textiles for their daily needs. However, with the acceleration of industrialization, a large amount of colored dye wastewater is discharged into the water environment, posing a serious threat to the environment and human health. In order to address the negative impact of textile wastewater discharge on the environment and health, effective wastewater treatment technologies and measures need to be adopted. Common textile wastewater treatment methods include biological, chemical and physical treatment methods. Among them, membrane separation has many advantages in textile wastewater treatment. For example, it can efficiently remove colored dyes from wastewater. In addition, membrane separation technology is simple to operate, the process is stable and reliable, and the equipment requirements are low. It is suitable for textile enterprises of all sizes.

[0003] It is worth noting that the presence of salt in textile wastewater hinders the biodegradation of dyes. In addition, these inorganic salts are also recyclable resources in textile wastewater. Therefore, separating the salt / dye mixture is a key step in reusing inorganic salts and treating textile wastewater. Nanofiltration (NF) membrane prepared by interfacial polymerization (IP) is one of the most representative NF membranes for dye / salt wastewater treatment. Currently, most NF membranes are polyamide (PA) membranes prepared from piperazine (PIP) and trimesoyl chloride (TMC). PA membranes generally have high dye removal rates and low monovalent salt (NaCl) rejection rates, so they can effectively separate dyes and monovalent salts. However, PA membranes still have high rejection of divalent salts (Na2SO4>90.00%) and low permeability (<10.0L·m -2 ·h -1 bar -1 ). Therefore, conventional NF membranes are not suitable for separating dye / salt mixtures.

[0004] To address existing issues, loose NF membranes have great potential because these membranes have higher water flux and dye rejection capabilities while allowing salt to pass through them. By separating dyes and salts, the content of harmful substances in wastewater can be effectively reduced, mitigating the impact on the environment and human health. Summary of the Invention

[0005] (1) Purpose of the invention

[0006] The purpose of the present invention is to propose a method for preparing a novel loose composite nanofiltration membrane based on the problems in the prior art such as low membrane permeability and high rejection rate of divalent salts, which cannot effectively separate salt and dye, so as to efficiently and stably treat dye wastewater.

[0007] (2) Technical solution

[0008] The present invention provides a method for preparing a novel loose composite nanofiltration membrane and its application in dye wastewater treatment, comprising the following steps:

[0009] Step 1: Preparation of monomers

[0010] 2,3,6,7,10,11-Hexahydroxytriphenyl (HHTP), copper acetate (Cu(CH3COO)2·H2O), N,N-dimethylformamide (DMF), and water were mixed and sealed in a 15 ml glass vial. After ultrasonic treatment for 15 minutes, the vial was heated at 85°C. After cooling to room temperature, the dark blue powder was collected by filtration, washed with water and methanol, and then air-dried to obtain Cu-HHTP.

[0011] Step 2: Preparation of aqueous and organic phase solutions

[0012] Preparation of aqueous solution: Piperazine (PIP) was dissolved in water to obtain a 1 wt% solution, and then different amounts of Cu-HHTP were added and mixed thoroughly to obtain an aqueous solution.

[0013] Preparation of organic phase solution: Dissolve trimesoyl chloride (TMC) in n-hexane to prepare an organic phase solution.

[0014] Step 3: Interfacial polymerization

[0015] A pre-treated commercial polyethersulfone (PES) support layer was removed from the DI water. Excess water droplets were carefully removed using an air knife, and the PES support layer was clamped with a flange. The aqueous solution was then deposited on the PES support layer for 60 seconds. After drying at room temperature, the organic solution was poured onto the PES support layer to initiate interfacial polymerization. The membrane surface was then rinsed with n-hexane to remove any residual TMC.

[0016] Step 4: Curing

[0017] The nanofiltration membrane prepared in step 3 is dried and solidified to obtain a TFN composite nanofiltration membrane;

[0018] Step 5: Take out the dried composite nanofiltration membrane and soak it in ultrapure water for subsequent use

[0019] In step 1, the amount of HHTP used is 32.4 mg, the amount of Cu(CH3COO)2·H2O used is 10.5 mg, and the amount of DMF and water used is 2.5 mL.

[0020] Wherein, in step 1, the heating time is 12 hours.

[0021] In step 2, the concentration of the PIP solution is 1 wt %, the volume is 10 ml, and the mass of Cu-HHTP is 0 mg, 1 mg, 5 mg, 7 mg, or 10 mg.

[0022] Wherein, in step 2, the concentration of the TMC organic phase solution is 0.1% and the volume is 10 ml.

[0023] In step 3, the TMC coverage time is 30s, 60s, 90s, 120s, or 150s.

[0024] Wherein, in step 4, the curing temperature is 60° C. and the curing time is 5 minutes.

[0025] (3) Beneficial effects

[0026] The above-mentioned technical solution describes a novel method for preparing a loose composite nanofiltration membrane. The novel loose composite nanofiltration membrane described in the above technical solution is prepared by monomer synthesis, aqueous solution preparation, and interfacial polymerization on a PAN-based membrane to produce a loose TFN nanofiltration membrane. The porous structure of the nanofiltration membrane can be finely tuned by adjusting the Cu-HHTP content or polymerization time. The introduction of Cu-HHTP into the polymerization reaction reduces the membrane's crosslinking degree and increases its surface hydrophilicity. Furthermore, the high porosity of the Cu-HHTP structure allows for the formation of faster water transport channels within the mixed matrix, improving the membrane's water permeability. Compared to the original thin film composite membrane, the membrane embedded with the optimized TFN membrane exhibits significant improvement in pure water permeability; furthermore, the TFN nanofiltration membrane maintains a high dye rejection rate. This study provides a novel method for preparing a loose composite nanofiltration membrane for the effective fractionation of dyes and salts from saline textile wastewater. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a graph showing the change in separation performance with different contents of Cu-HHTP;

[0028] Figure 2 This is a graph showing the changes in separation performance of the composite nanofiltration membranes prepared in Examples 1-5. DETAILED DESCRIPTION

[0029] In order to make the purpose, content and advantages of the present invention more clear, the specific implementation methods of the present invention are further described in detail below with reference to the accompanying drawings and examples.

[0030] This example uses two steps to determine the preparation of the novel loose composite nanofiltration membrane. First, the content of Cu-HHTP in the aqueous phase is determined, and then the time of interfacial polymerization is determined, thereby determining the optimal membrane preparation method.

[0031] The process for determining the Cu-HHTP content in the aqueous phase is as follows:

[0032] (1) 2,3,6,7,10,11-hexahydroxytriphenyl (HHTP), copper acetate (Cu(CH3COO)2·H2O), N,N-dimethylformamide (DMF), and water were mixed and sealed in a 15 ml glass vial. After ultrasonic treatment for 15 minutes, the vial was heated at 85°C. After cooling to room temperature, the dark blue powder was collected by filtration, washed with water and methanol, and then air-dried to obtain Cu-HHTP.

[0033] (2) Preparation of aqueous solution: Piperazine (PIP) was dissolved in water to obtain a 1 wt% solution. Subsequently, different amounts (0 mg, 1 mg, 5 mg, 7 mg, or 10 mg) of Cu-HHTP were added and mixed thoroughly to obtain an aqueous solution. Trimesoyl chloride (TMC) was dissolved in n-hexane to prepare an organic solution.

[0034] (3) Remove the pre-treated commercial polyethersulfone (PES) support layer from the DI water, carefully remove excess water droplets on the support layer using an air knife, and clamp the PES support layer with a flange. Then, cover the surface of the PES support layer with an aqueous solution and deposit it for a certain period of time. Dry at room temperature, then pour the organic solution onto the surface of the PES support layer to perform interfacial polymerization. Then, rinse the membrane surface with n-hexane to remove residual TMC on the surface. The interfacial polymerization time is 120 seconds, and then rinse the membrane surface with n-hexane to remove residual TMC on the surface.

[0035] (4) The membrane was placed in an oven at 60°C for heat treatment for 5 minutes to obtain a nanofiltration membrane.

[0036] In order to investigate the performance of the nanofiltration membrane, the experimental operating pressure was 4 bar and the experimental membrane area was 12.56 cm 2 The rejection of dyes (Congo Red (CR), Coomassie Brilliant Blue (G250), and Reactive Blue (RB19)) and salts (sodium sulfate (Na2SO4), sodium chloride (NaCl)) were tested to obtain the separation performance of the membrane. The feed concentrations of dyes and salts were kept at 0.2 g and 1.0 g / L, respectively. -1 , the volume is 1.0 L. Water flux J = ΔV / (A×T×P), where J is the water flux, ΔV is the water permeation volume (L), and A is the effective membrane area of ​​the nanofiltration membrane (m 2 ), T is time (h), P is pressure (bar) during filtration. The formula for calculating the salt and dye rejection reaction (R) is R=(1-C p / C f ), C P and C f represent the solute concentrations of the permeate solution and the feed solution, respectively.

[0037] After determining the optimal content of Cu-HHTP in the aqueous phase, the following examples were carried out.

[0038] Example 1

[0039] The preparation of the new loose composite nanofiltration membrane is as follows:

[0040] (1) 2,3,6,7,10,11-hexahydroxytriphenyl (HHTP), copper acetate (Cu(CH3COO)2·H2O), N,N-dimethylformamide (DMF), and water were mixed and sealed in a 15 ml glass vial. After ultrasonic treatment for 15 minutes, the vial was heated at 85°C. After cooling to room temperature, the dark blue powder was collected by filtration, washed with water and methanol, and then air-dried to obtain Cu-HHTP.

[0041] (2) Preparation of aqueous solution: Dissolve piperazine (PIP) in water to obtain a 1 wt% solution. Then add Cu-HHTP (7 mg) and mix thoroughly to obtain an aqueous solution. Dissolve trimesoyl chloride (TMC) in n-hexane to prepare an organic solution.

[0042] (3) Remove the pre-treated commercial polyethersulfone (PES) support layer from the DI water, carefully remove excess water droplets on the support layer using an air knife, and clamp the PES support layer with a flange. Then, cover the surface of the PES support layer with an aqueous solution and deposit it for a certain period of time. Dry at room temperature, then pour the organic solution onto the surface of the PES support layer to perform interfacial polymerization. Then, rinse the membrane surface with n-hexane to remove residual TMC on the surface. The interfacial polymerization time is 30 seconds, and then rinse the membrane surface with n-hexane to remove residual TMC on the surface.

[0043] (4) The membrane was placed in an oven at 60°C for heat treatment for 5 min to obtain the nanofiltration membrane TFN-1.

[0044] In order to investigate the performance of the nanofiltration membrane, the experimental operating pressure was 4 bar and the experimental membrane area was 12.56 cm 2 The rejection of dyes (Congo Red (CR), Coomassie Brilliant Blue (G250), and Reactive Blue (RB19)) and salts (sodium sulfate (Na2SO4), sodium chloride (NaCl)) were tested to obtain the separation performance of the membrane. The feed concentrations of dyes and salts were kept at 0.2 g and 1.0 g / L, respectively. -1 , the volume is 1.0 L. Water flux J = ΔV / (A×T×P), where J is the water flux, ΔV is the water permeation volume (L), and A is the effective membrane area of ​​the nanofiltration membrane (m 2 ), T is time (h), P is pressure (bar) during filtration. The formula for calculating the salt and dye rejection reaction (R) is R=(1-C p / C f), C P and C f represent the solute concentrations of the permeate solution and the feed solution, respectively.

[0045] Example 2

[0046] The preparation of the new loose composite nanofiltration membrane is as follows:

[0047] (1) 2,3,6,7,10,11-hexahydroxytriphenyl (HHTP), copper acetate (Cu(CH3COO)2·H2O), N,N-dimethylformamide (DMF), and water were mixed and sealed in a 15 ml glass vial. After ultrasonic treatment for 15 minutes, the vial was heated at 85°C. After cooling to room temperature, the dark blue powder was collected by filtration, washed with water and methanol, and then air-dried to obtain Cu-HHTP.

[0048] (2) Preparation of aqueous solution: Dissolve piperazine (PIP) in water to obtain a 1 wt% solution. Then add Cu-HHTP (7 mg) and mix thoroughly to obtain an aqueous solution. Dissolve trimesoyl chloride (TMC) in n-hexane to prepare an organic solution.

[0049] (3) Remove the pre-treated commercial polyethersulfone (PES) support layer from the DI water, carefully remove excess water droplets on the support layer using an air knife, and clamp the PES support layer with a flange. Then, cover the surface of the PES support layer with an aqueous solution and deposit it for a certain period of time. Dry at room temperature, then pour the organic solution onto the surface of the PES support layer to perform interfacial polymerization. Then, rinse the membrane surface with n-hexane to remove residual TMC on the surface. The interfacial polymerization time is 60 seconds, and then rinse the membrane surface with n-hexane to remove residual TMC on the surface.

[0050] (4) The membrane was placed in an oven at 60°C for heat treatment for 5 min to obtain the nanofiltration membrane TFN-2.

[0051] In order to investigate the performance of the nanofiltration membrane prepared in the example, the specific testing process was consistent with that in Example 1.

[0052] Example 3

[0053] The preparation of the new loose composite nanofiltration membrane is as follows:

[0054] (1) 2,3,6,7,10,11-hexahydroxytriphenyl (HHTP), copper acetate (Cu(CH3COO)2·H2O), N,N-dimethylformamide (DMF), and water were mixed and sealed in a 15 ml glass vial. After ultrasonic treatment for 15 minutes, the vial was heated at 85°C. After cooling to room temperature, the dark blue powder was collected by filtration, washed with water and methanol, and then air-dried to obtain Cu-HHTP.

[0055] (2) Preparation of aqueous solution: Dissolve piperazine (PIP) in water to obtain a 1 wt% solution. Then add Cu-HHTP (7 mg) and mix thoroughly to obtain an aqueous solution. Dissolve trimesoyl chloride (TMC) in n-hexane to prepare an organic solution.

[0056] (3) Remove the pre-treated commercial polyethersulfone (PES) support layer from the DI water, carefully remove excess water droplets on the support layer using an air knife, and clamp the PES support layer with a flange. Then, cover the surface of the PES support layer with an aqueous solution and deposit it for a certain period of time. Dry at room temperature, then pour the organic solution onto the surface of the PES support layer to perform interfacial polymerization. Then, rinse the membrane surface with n-hexane to remove residual TMC on the surface. The interfacial polymerization time is 90 seconds, and then rinse the membrane surface with n-hexane to remove residual TMC on the surface.

[0057] (4) The membrane was placed in an oven at 60°C for heat treatment for 5 min to obtain the nanofiltration membrane TFN-3.

[0058] In order to investigate the performance of the nanofiltration membrane prepared in the example, the specific testing process was consistent with that in Example 1.

[0059] Example 4

[0060] The preparation of the new loose composite nanofiltration membrane is as follows:

[0061] (1) 2,3,6,7,10,11-hexahydroxytriphenyl (HHTP), copper acetate (Cu(CH3COO)2·H2O), N,N-dimethylformamide (DMF), and water were mixed and sealed in a 15 ml glass vial. After ultrasonic treatment for 15 minutes, the vial was heated at 85°C. After cooling to room temperature, the dark blue powder was collected by filtration, washed with water and methanol, and then air-dried to obtain Cu-HHTP.

[0062] (2) Preparation of aqueous solution: Dissolve piperazine (PIP) in water to obtain a 1 wt% solution. Then add Cu-HHTP (7 mg) and mix thoroughly to obtain an aqueous solution. Dissolve trimesoyl chloride (TMC) in n-hexane to prepare an organic solution.

[0063] (3) Remove the pre-treated commercial polyethersulfone (PES) support layer from the DI water, carefully remove excess water droplets on the support layer using an air knife, and clamp the PES support layer with a flange. Then, cover the surface of the PES support layer with an aqueous solution and deposit it for a certain period of time. Dry at room temperature, then pour the organic solution onto the surface of the PES support layer to perform interfacial polymerization. Then, rinse the membrane surface with n-hexane to remove residual TMC on the surface. The interfacial polymerization time is 120 seconds, and then rinse the membrane surface with n-hexane to remove residual TMC on the surface.

[0064] (4) The membrane was placed in an oven at 60°C for heat treatment for 5 min to obtain the nanofiltration membrane TFN-4.

[0065] In order to investigate the performance of the nanofiltration membrane prepared in the example, the specific testing process was consistent with that in Example 1.

[0066] Example 5

[0067] The preparation of the new loose composite nanofiltration membrane is as follows:

[0068] ((1) 2,3,6,7,10,11-hexahydroxytriphenyl (HHTP), copper acetate (Cu(CH3COO)2·H2O), N,N-dimethylformamide (DMF) and water were mixed and sealed in a 15 ml glass vial. After ultrasonic treatment for 15 min, the vial was heated at 85°C. After cooling to room temperature, the dark blue powder was collected by filtration, washed with water and methanol, and then air-dried to obtain Cu-HHTP;

[0069] (2) Preparation of aqueous solution: Dissolve piperazine (PIP) in water to obtain a 1 wt% solution. Then add Cu-HHTP (7 mg) and mix thoroughly to obtain an aqueous solution. Dissolve trimesoyl chloride (TMC) in n-hexane to prepare an organic solution.

[0070] (3) Remove the pre-treated commercial polyethersulfone (PES) support layer from the DI water, carefully remove excess water droplets on the support layer using an air knife, and clamp the PES support layer with a flange. Then, cover the surface of the PES support layer with an aqueous solution and deposit it for a certain period of time. Dry at room temperature, then pour the organic solution onto the surface of the PES support layer to perform interfacial polymerization. Then, rinse the membrane surface with n-hexane to remove residual TMC on the surface. The interfacial polymerization time is 150 s, and then rinse the membrane surface with n-hexane to remove residual TMC on the surface.

[0071] (4) The membrane was placed in an oven at 60°C for heat treatment for 5 min to obtain the nanofiltration membrane TFN-5.

[0072] In order to investigate the performance of the nanofiltration membrane prepared in the example, the specific testing process was consistent with that in Example 1.

[0073] Experimental results:

[0074] from Figure 1 It can be determined that the optimal content of Cu-HHTP in the aqueous phase is 7 mg; Figure 2 It can be found that the pure water flux of the nanofiltration membrane gradually decreases from 30s to 90s, and the pure water flux remains basically unchanged after 90s. When the interfacial polymerization time is 120s, the water flux of the composite membrane is 46.7Lm -2 h -1bar -1 The removal rates of Congo red, reactive blue and Coomassie brilliant blue were 99.6%, 99% and 98.5% respectively, and the removal rates of sodium chloride and sodium sulfate were 16% and 26.5% respectively.

[0075] From the results, it can be found that the new loose composite nanofiltration membrane obtained has a relatively low rejection effect on divalent salts while maintaining high separation performance for dyes. Compared with existing membranes, the composite nanofiltration membrane has good application prospects for treating dye wastewater.

[0076] It can be seen from the above technical solution that the present invention has the following significant features:

[0077] The novel loose composite nanofiltration membrane described in the above technical solution is prepared by monomer synthesis, aqueous solution preparation, and interfacial polymerization on a PES-based membrane to produce a loose TFN nanofiltration membrane. The introduction of CU-HHPT into the polymerization reaction reduces the membrane's crosslinking degree and improves its surface hydrophilicity. Furthermore, the high porosity of the CU-HHPT structure allows for the formation of faster water transport channels within the mixed matrix, enhancing the membrane's water permeability. Compared to the original thin-film composite membrane, the optimal membrane, TFN-4, exhibited a significant improvement in pure water permeability, increasing by 5.8 times, while maintaining a high dye retention rate.

[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a novel loose composite nanofiltration membrane for treating dye wastewater, characterized in that: The following steps are involved: Step 1: Preparation of monomers 2,3,6,7,10,11-hexahydroxytriphenyl (HHTP), copper acetate (Cu(CH3COO)2·H2O), N,N-dimethylformamide (DMF) and water were mixed and sealed in a 15 ml glass vial. After ultrasonic treatment for 15 minutes, the vial was heated at 85°C. After cooling to room temperature, the dark blue powder was collected by filtration, washed with water and methanol, and then air-dried to finally obtain Cu-HHTP. Step 2: Preparation of aqueous and organic phase solutions Preparation of aqueous phase solution: piperazine (PIP) was dissolved in water to obtain a 1 wt% solution, and then different amounts of Cu-HHTP were added and mixed thoroughly to obtain an aqueous phase solution. Preparation of organic phase solution: Dissolve trimesoyl chloride (TMC) in n-hexane to prepare an organic phase solution. Step 3: Interface polymerization Take out the pre-treated commercial polyethersulfone (PES) support layer from DI water, carefully remove excess water droplets on the support layer with an air knife, and clamp the PES support layer with a flange. Then cover the surface of the PES support layer with an aqueous solution and deposit it for 60 seconds. Dry at room temperature, then pour the organic solution onto the surface of the PES support layer for interfacial polymerization. The interfacial polymerization time is 30-150 seconds, and then rinse the membrane surface with n-hexane to remove the residual TMC on the surface. Step 4: Curing The nanofiltration membrane prepared in step 3 is dried and solidified to obtain a TFN composite nanofiltration membrane; Step 5: Take out the dried composite nanofiltration membrane and soak it in ultrapure water for subsequent use.

2. The preparation of the novel loose composite nanofiltration membrane according to claim 1, characterized in that: In step 1, the amount of HHTP used is 32.4 mg, the amount of Cu(CH3COO)2·H2O used is 10.5 mg, and the amount of DMF and water used is 2.5 mL.

3. The preparation of the novel loose composite nanofiltration membrane according to claim 2, characterized in that: In step 1, the heating time is 12 hours.

4. The preparation of the novel loose composite nanofiltration membrane according to claim 3, characterized in that: In step 2, the concentration of the PIP solution is 1 wt %, the volume is 10 ml, and the mass of Cu-HHTP is 0 mg, 1 mg, 5 mg, 7 mg, or 10 mg.

5. The preparation of the novel loose composite nanofiltration membrane according to claim 4, characterized in that: In step 2, the concentration of TMC in the organic phase solution is 0.1 wt %.

6. The preparation of the novel loose composite nanofiltration membrane according to claim 5, characterized in that: In step 3, the time of interfacial polymerization is 30 s, 60 s, 90 s, 120 s, or 150 s.

7. The preparation of the novel loose composite nanofiltration membrane according to claim 6, characterized in that: In step 3, the curing temperature is 60° C. and the curing time is 5 min.

8. A novel loose composite nanofiltration membrane, characterized in that: Prepared by the preparation method described in any one of claims 1 to 7.

9. A preparation method of a novel loose composite nanofiltration membrane according to any one of claims 1 to 7 and its application in the field of membrane separation technology.

10. An application of the novel loose composite nanofiltration membrane according to claim 8 in the field of membrane separation technology.